2020
DOI: 10.3389/fmicb.2020.00569
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Snow Algae Blooms in the Coast Range of British Columbia

Abstract: Snow algae blooms cover vast areas of summer snowfields worldwide, reducing albedo and increasing snow melt. Despite their global prevalence, little is known about the algae species that comprise these blooms. We used 18S and rbcL metabarcoding and light microscopy to characterize algae species composition in 31 snow algae blooms in the Coast Range of British Columbia, Canada. This study is the first to thoroughly document regional variation between blooms. We found all blooms were dominated by the genera Sang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 44 publications
(65 reference statements)
0
29
0
Order By: Relevance
“…In the current study, we set out to robustly document the microbial diversity in the mountains of Southwestern British Columbia. Previously, we reported that Sanguina and Chloromonas dominated distinct blooms and that they were found at different elevations (Engstrom et al, 2020). Based on the work of Terashima et al (2017) and Krug et al (2020), we predicted that specific microbial taxa would be associated with the distinct algal blooms.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…In the current study, we set out to robustly document the microbial diversity in the mountains of Southwestern British Columbia. Previously, we reported that Sanguina and Chloromonas dominated distinct blooms and that they were found at different elevations (Engstrom et al, 2020). Based on the work of Terashima et al (2017) and Krug et al (2020), we predicted that specific microbial taxa would be associated with the distinct algal blooms.…”
Section: Introductionmentioning
confidence: 92%
“…The families of Ochorophyta detected included Chrysophyceae, Chrysocapsales, Mallomonadaceae, and Xanthophyceae. For a higher resolution analysis of the algal communities within our study region see Engstrom et al (2020).…”
Section: Algal Community Compositionmentioning
confidence: 99%
“…The blooms occurred at open sites with elevation ranging from 1862 to 3500 m (this study), but earlier studies reported C. krienitzii to be predominant in clearings or sites with sparse trees around 1200 m (Engstrom et al, 2020) or at open sites in broad-leaf forest around 880 m elevation (R. Matsuzaki-pers. comm., Matsuzaki et al, 2015).…”
Section: Species Distribution Along the Gradient Of Elevationsmentioning
confidence: 54%
“…Individual species of snow algae can either show a cosmopolite distribution (e.g., S. nivaloides, Segawa et al, 2018;Procházková et al, 2019a) or their known occurrence is rather geographically limited (e.g., Chloromonas polyptera, Remias et al, 2013; Sanguina aurantia, Brown and Tucker, 2020). C. krienitzii seems to be in-between: It was initially described only from Japan (Matsuzaki et al, 2015) and subsequently found in Europe and North America as well (this study, Engstrom et al, 2020). Likely, the morphologically striking cysts have been observed many times elsewhere, but were determined as Chloromonas cf.…”
Section: Geographical Distribution Of Snow Algaementioning
confidence: 57%
See 1 more Smart Citation